(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The former Prime Minister of India, Dr. Manmohan Singh approved the constitution of the ‘Seventh Central Pay Commission (CPC)’ for revising the salary and other benefits of eight million central government employees and pensioners after seven years of sixth pay commission. The sitting of Seventh Pay Commission was declared just before the election. The expected benefits to the Government employees and pensioners would be considerable. The main objective of the research is to study the earlier pay commissions and their impact on income distribution in India. The study found that the implementation of earlier Central Pay Commission (CPC) recommendations put tremendous pressure on the state exchequer. Although beneficiaries of CPC recommendations would enjoy good life, the number is negligible. The paper also compiles researcher opinions and comments from industry bodies. In this paper, the author puts forth the stories of exploitation of private employees which the victims described during interaction. This paper aims to help the reader study the impact of seventh pay commission from different angles and would probably suggest to the Government of India to take a fresh look to the issue.